A Sensitive Two-Analyte Immunochromatographic Strip for Simultaneously Detecting Aflatoxin M1 and Chloramphenicol in Milk - Shih-Wei Wu; Jiunn-Liang Ko; Biing-Hui Liu; Feng-Yih Yu (Toxins, 2020)
A two-analyte immunochromatographic strip (immunostrip) was developed for the simultaneous detection of aflatoxin M1 (AFM1) and chloramphenicol (CAP) in milk. Protein conjugates (AFM1-ovalbumin (OVA) and CAP-OVA) and goat anti-rabbit IgG were respectively drawn on nitrocellulose membrane as two test lines (T1 and T2) and a control line (C). The immunostrip was dipped into a well that contained a 200 μL milk sample, 5 μL AFM1 antibody-gold conjugates, and 8 μL CAP antibody-gold conjugates; the whole assay was completed in 15 min and the results could be interpreted visually or using a reader. This immunostrip has cut-off levels of 0.1 ng/mL and 0.5 ng/mL for AFM1 and CAP, respectively. Analysis of CAP and AFM1 in milk samples revealed that data from the immunostrip test agreed closely with those obtained from ELISA. The two-analyte immunostrip is a rapid way for on-site simultaneous detection of AFM1 and CAP in milk.